The Reality of Scientific Research in the General Educational Schools of Qatif Hopes and Aspirations to Achieve the Saudi Vision 2030 - Al-Obaidan, Safieh Saeed; Al-Zahrani, Nawal Deifallah; Al Samah, Layl Said Ashour; Al-Khalidi, Noura Awad (Journal of Educational and Psychological Sciences, 2019)
The aim of this study is to identify the reality of scientific research in the office and schools of general education in Qatif Governorate from the point of view of educators and students, and to highlight the efforts of the Ministry of Education in establishing the research base in the educational field. The study used the Descriptive analytical method and three research tools: electronic questionnaire, interviews and discussion sessions, which were applied to a random sample of (942) female educators and students in Qatif Education Office and schools. Of these, (818) responded to the questionnaire and (24) were supervisors who shared in the interviews, and (100) students participated in (5) panel discussion focused groups, each one consisted of (20) participants. The study found that only 32% of the sample participated in training programs for scientific research skills (80.8%) attended the training program for scientific research in the Ministry, and (88%) of the participants supported the establishment of a scientific research department, (73%) believes that the Ministry of Education has formulated a clear plan to achieve the vision of the Kingdom 2030 to support and disseminate scientific research, while more than (63%) believes that scientific research related to educational problems in the educational field helps in planning well and effectively for education. Also, (65%) believe that the lack of competencies is one of the most important obstacles to the spread of scientific research. Finally, (66%) believes the pressures of work and study requirements of the most important reasons for refraining from writing educational scientific research. As demonstrated by the results of the hypothesis test; there is a strong correlation relationship reached (0.98) between the obstacles of scientific research in schools and the weak outputs of educational research, and the existence of a strong correlation relationship reached (0.95) between the efforts of the Ministry of Education in supporting scientific research and its impact on achieving the vision of the Kingdom 2030, (84%) confirms that scientific research on educational problems helps to develop education. In the light of these results, a number of recommendations and suggestions have been presented, including: forming a scientific research council in Qatif Education Office and in all education offices in the Kingdom, taking advantage of the experiences of universities in scientific research to transfer them to public education schools, provide specialized training crews to spread the culture of scientific research in the educational field, organize the establishment of forums, exhibitions and scientific conferences to present the results of students’ research and educational staff to benefit from them, and the adoption of scientific research standard of the differentiation of supervisory and administrative positions.